Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Join our platform to connect with experts ready to provide detailed answers to your questions in various areas. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

(11m-7m)-(2m+6m) the sum or differce

Sagot :

Prohor

Answer:

-4m

Step-by-step explanation:

=11m-7m-(2m+6m)

=11m-7m-8m

=-4m

plz mark me as brainliest

Answer:

-4m

Step-by-step explanation:

Hey!

==================================================================

First, We should remove the Parentheses.

To remove them, we distribute the negative over (2m + 6m).

⇒ 11m - 7m - (2m + 6m)

⇒ 11m - 7m - 2m - 6m

Work the Problem from Left to Right.

⇒ 4m - 2m - 6m

⇒ 2m - 6m

-4m

==================================================================

Hope I Helped, Feel free to ask any questions to clarify :)

Have a great day!

More Love, More Peace, Less Hate.

       -Aadi x

We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.